HUBUNGAN ANTARA KADAR LIPOPROTEIN A SERUM DENGAN KELUARAN PASIEN STROKE ISKEMIK AKUT - Dewi Hastuty,* Endang Kustiowati,* Dwi Pudjonarko* (NEURONA, 2015)
INTRODUCTION ELEVATED LEVEL OF LIPOPROTEINA LPA IS AN INDEPENDENT RISK FACTOR FOR ISCHEMIC STROKE AND MAY BE ASSOCIATED WITH ITS OUTCOME IN INDONESIA DATA REGARDING CORRELATION BETWEEN LPA LEVEL AND THE OUTCOME OF ISCHEMIC STROKE PATIENTS ISLIMITED